Peran Lembaga Swadaya Masyarakat Dalam Penguatan Pemerintahan Lokal - Rinawati Rinawati; Nusyirwan Effendi (Jurnal Administrasi dan Kebijakan Publik, 2022)
Development is a must and important in an effort to create community welfare. In carrying out development, it is necessary to cooperate with the government as a development coordinator with parties outside the government who have sensitivity and a sense of social responsibility for development in the community. Community Social Institutions (NGOs) are institutions from the community that can be used as government partners in community development. This program is supported by increasing the capacity of institutions and the community itself through training and counseling. The role of NGOs in strengthening local government, the results obtained are at the structural stage. This means that we can only see the birth of a local government structure which in fact originates from the desire of the community that is formed in a participatory manner. However, to see the role of government that influences the development and welfare of the community, this is still not seen in a concrete way. This is in accordance with the concept of empowerment that empowerment is a process. Local government or empowerment cannot be done in a short time pheriod. Sustainability in this program is needed until the local government can truly be empowered or independent. To increase local government independence, not only carried out by NGOs, but all of relevant parties such as the Regional Government, the Community, and the local government it self, there must be efforts to increase empowerment